Digital Pathology Investigation of SERPINA5‐Tau Protein Interaction in Alzheimer's Disease and Primary Tauopathies. (20th December 2022) - Sirmans, Tiffany N. Hicks; Kouri, Naomi; Tamvaka, Nicole; Labuzan, Sydney A; Matchett, Billie J; Lincoln, Sarah J.; Hinkle, Kelly M; Moloney, Christina M.; Peng, Zhongwei; Carter, Rickey E; Ross, Owen A.; Ertekin‐Taner, Nilufer; et al.
Abstract: Background: We recently discovered a novel tau binding partner, SERPINA5, to be upregulated in Alzheimer's disease (AD) and co‐localize with corticolimbic tau distribution. As tau pathology is also observed in primary tauopathies, we hypothesized that SERPINA5 burden would mirror tau burden in these diseases. Thus, we sought to define the relationship between SERPINA5 and tau in primary tauopathies and compare this relationship to AD. Method: Immunohistochemistry was performed on the hippocampus or cingulate in 4 groups (n=6 per disease group): 1) AD, 2) 3R+4R primary age‐related tauopathy, 3) 4R tauopathies (progressive supranuclear palsy, corticobasal degeneration, argyrophilic grains disease), and 4) 3R tauopathy (Pick's disease). Burden analyses for SERPINA5 and a phospho‐tau marker (AT8) were performed on digitized whole slide images. Result: Visual interpretation of SERPINA5 immunostaining identified both neuronal and glial inclusions that are commonly AT8‐positive in primary tauopathies. There were exceptions to this pattern such as SERPINA5‐positive Pick bodies being rarely observed. However, some pathologic structures, like ballooned neurons, were preferentially stained by SERPINA5. Quantitative analyses confirmed this observation with AT8 and SERPINA5 burden correlating in both the cingulate (R 2 =0.47, p<0.0001, Figure 1a ) and hippocampus (R 2 =0.74, p<0.0001, Figure 1d ). Nonparametric rank sum tests revealed majority of the primary tauopathies had less AT8 and SERPINA5 burden compared to AD in both the cingulate and hippocampus (Figure1b‐c, e‐f; Table 1 ). Conclusion: SERPINA5 immunostaining patterns in primary tauopathies reflect tau immunostaining patterns. Our data suggests the SERPINA5‐tau interaction may not be specific for AD, which may implicate the role of SERPINA5 more broadly across tauopathies.